PENGARUH E-WOM FACEBOOK TERHADAP MINAT BELI MAHASISWA PEREMPUAN BERBELANJA ONLINE (STUDI PADA FAKULTAS EKONOMI USI PEMATANGSIANTAR, SUMATERA UTARA, INDONESIA) - Liharman Saragih (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2020)
Abstract This study aims to determine how the influence of E-WOM Facebook on the purchase intention of female students of Fakultas Ekonomi USI on shopping online. The results showed that online review had an effect of 76.1%. according to independent variables are seen the variable